2011
DOI: 10.1111/j.1537-2995.2011.03247.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion‐associated circulatory overload after plasma transfusion

Abstract: Passive reporting of TACO grossly underestimates its actual prevalence. Educational efforts are needed to enhance physician recognition of TACO reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
133
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 15 publications
7
133
2
5
Order By: Relevance
“…Circulatory overload as seen in TACO is one of the most frequent potentially severe complication of RBC transfusion [16]. Unfortunately, it is also one of the most underreported and under-diagnosed complication of BT [17,18]. An active surveillance system as demonstrated in our study can improve reporting of such complications and prevent such potential morbidities and mortalities due to BT.…”
Section: Discussionmentioning
confidence: 84%
“…Circulatory overload as seen in TACO is one of the most frequent potentially severe complication of RBC transfusion [16]. Unfortunately, it is also one of the most underreported and under-diagnosed complication of BT [17,18]. An active surveillance system as demonstrated in our study can improve reporting of such complications and prevent such potential morbidities and mortalities due to BT.…”
Section: Discussionmentioning
confidence: 84%
“…Plasma-induced TACO has been estimated to be drastically underreported, and the prevalence may be significantly higher than commonly thought. 30 Even without the potential adverse effects related to the volumes of fluid required in FP, the time necessary to prepare and complete the infusion safely may result in a lengthy duration of treatment. Other risks related to FP transfusion, such as TRALI, pathogen transmission, and severe allergic reactions, should also be weighed as risks when considering the use of FP.…”
Section: Contraindicationsmentioning
confidence: 99%
“…Other risks related to FP transfusion, such as TRALI, pathogen transmission, and severe allergic reactions, should also be weighed as risks when considering the use of FP. 27,30 Despite published guidelines for FP transfusion, a recent five-day audit of FP utilization in 76 hospitals in Ontario found that, overall, only 29% of patients transfused with FP received optimal therapy, including both the correct dose and the appropriate indication for use. 31 The most common inappropriate uses for FP were for patients with an INR \ 1.5 or when administered to patients for warfarin reversal in the absence of bleeding.…”
Section: Contraindicationsmentioning
confidence: 99%
See 2 more Smart Citations